Missing a Phage: Unraveling Tripartite Symbioses within the Human Gut - Jeremy J. Barr (mSystems, 2019)
Tripartite symbioses between bacteriophages, the epithelial cell layers of the human gut, and bacterial symbionts may play an important and unrecognized role in the function of the gut microbiome. Traditionally, phages residing within the gut were considered to interact only with their bacterial hosts and thereby to facilitate indirect interactions with the epithelial cell layers, and yet a growing body of literature is demonstrating the surprising and diverse ways in which phages directly interact with the eukaryotic cells, organs, and systems of the body.Tripartite symbioses between bacteriophages, the epithelial cell layers of the human gut, and bacterial symbionts may play an important and unrecognized role in the function of the gut microbiome. Traditionally, phages residing within the gut were considered to interact only with their bacterial hosts and thereby to facilitate indirect interactions with the epithelial cell layers, and yet a growing body of literature is demonstrating the surprising and diverse ways in which phages directly interact with the eukaryotic cells, organs, and systems of the body. Phages can adhere to mucosal surfaces, bind and transcytose epithelial cells, and deliver proteins and nucleic acids to eukaryotic cells directly. These interactions could establish positive-feedback loops leading to the selection of bacterial hosts and their phage symbionts in the gut. The members of my laboratory are working to expand our knowledge on the phage-eukaryote interactions and to redefine the concept of tripartite symbioses within the human body.